A method for determining the complex value of technical losses of full power in power three-phase two-winding transformers with account of additional losses from higher harmonic components - S. S. Kostinskiy; A. V. Bogdan; E. I. Satsuk; A. S. Zasypkin (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. In recent years, there has been a significant deterioration in the quality of electrical energy in the networks of industrial and non-industrial consumers as more and more electric receivers with nonlinear volt-ampere characteristics generating higher harmonic current components in the network are connected to them. The higher harmonic components of the current create additional losses in the transformer windings and additional losses on eddy currents in the magnetic circuit. All this leads to a decrease in the efficiency of electricity transmission processes and a reduction in the estimated service life of electrical equipment and electrical networks.Goal. The study develops and test a methodology for determining the complex value of technical losses of full power in power three-phase two-winding transformers, taking into account additional losses from higher harmonic components.Materials and methods. To implement the technique, a T-shaped replacement circuit of a three-phase two-winding power transformer is used, which is assumed to be symmetrical. To perform calculations using the proposed technique, passport data of a three-phase two-winding power transformer are required. Along with the study requires the data (active power, current and voltage) measured for each of the three phases and for each harmonic component starting from the 1st to the 40th using measuring instruments installed in the input cell supplying low-voltage busbars of a transformer substation, to which the final consumer of electrical energy is connected.Results and discussion. The approbation of the developed methodology was carried out by the example of an existing power supply system supplying a metal galvanizing workshop, which includes a three-phase two-winding power transformer of the TMZ brand with a nominal capacity of 1000 kV •A. The measured data on the magnitude and harmonic composition of the current strength, active power and supply voltage were obtained using an electric energy quality analyzer Energomonitor 3.3 T installed in the input cell feeding the low-voltage busbars of a transformer substation. Based on the results of the approbation, the complex value of the technical losses of full power in a power three-phase two-winding transformer is calculated, taking into account additional losses from higher harmonic components.Conclusion. The developed technique makes it possible to increase the accuracy of determining the complex value of technical losses of full power in power three-phase double-winding transformers operated in urban and industrial power supply systems by taking into account additional losses associated with the presence of higher harmonic components in the power supply system due to the presence of a nonlinear electrical load.